Physico-nutritional attributes and pathogen contamination of lettuce (Lactuca sativa) grown in vermicompost-ameliorated soil - Laspiñas, Cherry Mae Javier
The effects of vermicompost on the growth and physico-nutritional content of lettuce were assessed through a pot experiment under greenhouse conditions on February to May 2006 in UPV, Miagao.